METHODS OF THE MILITARY-PEDAGOGICAL RESEARCH AND DEVELOPMENT - Kozhedub, O.; Gavryushenko, V.; Levenets, A. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2022)
The article authors basing on the analysis of recent publications and the scientific research results of pedagogical and military-pedagogical issues, establish that there are almost no fundamental methodological studies in military-pedagogical science. It is noted that integration processes are observed in the application of methodological tools. The author’s team draws readers’ attention to the fact that modern military-pedagogical science uses methods of scientific search, which are actively used by such sciences as logic, sociology, psychology, economics and some others. The article describes and provides examples of the application of a number of methods that are used by the above mentioned sciences. Such methods are: the method of expert assessments, which allows to obtain and summarize the opinions of experts on the subject of scientific research; systematisation and classification, which allows to organize many phenomena, processes, and facts; forecasting, which is based on actions to obtain, process and generate information about the future; monitoring, which is a continuous and long-term observing of the course of military-pedagogical events and processes; sociometric method, which is used for intra-group processes diagnostics; content analysis, it is a method of qualitative and quantitative analysis of the content of a document that allows to perform an off-text reality deep analysis; methods of mathematical and statistical processing of the obtained empirical data. In conclusion, the authors note the need for a thorough methodological study of the features of applying the military-pedagogical scientific methods, the results of which would be used as representatives of militarypedagogical theory and practice.